Video Review Can Measure Surgical Robotic Skill Development in a Resident Robotic Hernia Curriculum: A Retrospective Cohort Study - Sarah B. Hays, MD; Amr I. Al Abbas, MD; Kristine Kuchta, MS; Aram Rojas, MD; Melissa Ramirez Barriga, BS; Syed Abbas Mehdi, MBBS, MPH; Stephen Haggerty, MD; H. Mason Hedberg, MD; John Linn, MD; Mark Talamonti, MD; Melissa E. Hogg, MD, MS (Annals of Surgery Open)
Background:. Hernia repairs are one of the most common general surgery procedures and an essential part of training for general surgery residents. The widespread incorporation of robotic hernia repairs warrants the development of a procedure-specific robotic curriculum to assist novice surgeons in improving technical skills. Objective:. To evaluate a robotic hernia simulation-based curriculum for general surgery residents using video review. Methods:. Retrospective cohort study of PGY-3 general surgery residents from the University of Chicago from 2019 to 2021. The residents completed inguinal hernia repair (IHR) and ventral hernia repair (VHR) drills as part of a robotic simulation curriculum. The drills were recorded and graded according to the modified objective structured assessment of technical skills (OSATS) and time to completion. The drills were completed by 3 attending surgeons to establish gold-standard benchmarks. Results:. In total, 20 residents started the curriculum, 19 completed all IHR drills and 17 completed all VHR drills. Attending surgeon total OSATS scores and time to completion were significantly better than the trainees on the first attempt (P < 0.05). When comparing 1st to 4th attempt, resident OSATS scores improved significantly for IHR (15.5 vs 23.3; P < 0.001) and VHR (16.8 vs 23.3; P < 0.001). Time also improved over 4 attempts (IHR: 28.5 vs 20.5 minutes; P < 0.001 and VHR: 29.6 vs 21.2 minutes; P < 0.001). Residents achieved attending-level OSATS scores by their fourth attempt for VHR, but not for IHR. Residents did not achieve attending-level times for either hernia drills. Conclusions:. The robotic hernia curriculum improved resident performance on hernia repair drills and was well-received by the residents.